2021
DOI: 10.21203/rs.3.rs-1044264/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Alterations in Cortisol and Interleukin-6 Secretion in Patients With COVID-19 Suggestive of Neuroendocrine-Immune Adaptations

Abstract: Purpose: The beneficial effect of glucocorticoids in coronavirus disease (COVID-19) is established, but whether adrenal cortisol secretion is impaired in COVID-19 is not fully elucidated. In this case-control study we investigated the diurnal free bioavailable salivary cortisol secretion in COVID-19 patients.Methods: Fifty-two consecutive COVID-19 patients -before dexamethasone treatment- recruited between April 15th -June15th-2021, (NCT04988269) at Laikon Athens University-Hospital, and 33 healthy age- and se… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 31 publications
(15 reference statements)
0
2
0
Order By: Relevance
“…In contrast to the majority of studies that only measured morning total cortisol concentrations, a recent study determined the free salivary cortisol levels of COVID-19 patients at different time points. Interestingly, this study reported elevated levels of free cortisol also during the evening (0.391 vs. 0.081 μg/dl) and nocturnal (0.183 vs. 0.054 μg/dl) time points in the mild-to-moderate COVID-19 group compared to healthy individuals 65 . However, ACTH, DHEA, and aldosterone concentrations were not altered suggesting an intact adrenal structure 65 .…”
Section: Introductionmentioning
confidence: 47%
See 1 more Smart Citation
“…In contrast to the majority of studies that only measured morning total cortisol concentrations, a recent study determined the free salivary cortisol levels of COVID-19 patients at different time points. Interestingly, this study reported elevated levels of free cortisol also during the evening (0.391 vs. 0.081 μg/dl) and nocturnal (0.183 vs. 0.054 μg/dl) time points in the mild-to-moderate COVID-19 group compared to healthy individuals 65 . However, ACTH, DHEA, and aldosterone concentrations were not altered suggesting an intact adrenal structure 65 .…”
Section: Introductionmentioning
confidence: 47%
“…Interestingly, this study reported elevated levels of free cortisol also during the evening (0.391 vs. 0.081 μg/dl) and nocturnal (0.183 vs. 0.054 μg/dl) time points in the mild-to-moderate COVID-19 group compared to healthy individuals 65 . However, ACTH, DHEA, and aldosterone concentrations were not altered suggesting an intact adrenal structure 65 . On the contrary, a possible disruption of adrenocortical steroidogenesis in patients with more severe COVID-19 was recently reported 66 .…”
Section: Introductionmentioning
confidence: 47%